Commonwealth Secretariat annual results report 2013 / 2014 (The Secretariat LondonGB, 2015)
Summarises the Secretariat's performance in the first year of the Strategic Plan 2013/14 - 2016/17. Commences with a brief description of the work area, followed by a short description of significant results achieved during the reporting period. Reports on enabling outcomes.
Keywords: COMMONWEALTH